Implementasi Teknologi Cloud Computing Di Perguruan Tinggi - Bahono, Humam Binafidz; Sinta Rohmatin; Aysah Sinta Wati; Dewi Setyaningrum (CV.ITTC INDONESIA, 2025)
The development of information technology has driven digital transformation in various fields, including the higher education sector. One technology that plays a crucial role in this process is cloud computing, which offers elastic, flexible, and efficient computing services over the internet. This study uses a qualitative descriptive method to describe and analyze the implementation of cloud computing technology in higher education institutions based on a literature review from various relevant sources. The study focuses on the benefits gained, challenges faced, and possible implementation strategies. The analysis shows that cloud computing technology can improve operational efficiency, expand access to data and academic services, and strengthen collaboration among academics. However, several obstacles need to be anticipated, particularly those related to data security, network infrastructure reliability, and human resource readiness. These findings are expected to serve as a reference for higher education institutions in planning effective and sustainable cloud computing implementation.